2020
DOI: 10.1177/0218492320963976
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transhiatal esophagectomy using a mediastinoscope with transhiatal esophagectomy by the classic method

Abstract: Background This study aimed to evaluate the results of transhiatal esophagectomy using a mediastinoscope in comparison with conventional transhiatal esophagectomy. Methods Sixty-two esophageal cancer patients who were referred to our thoracic surgery clinic between April 2015 and March 2017, and met the inclusion criteria, were randomly divided into two groups of 31 each. In the first group, patients were operated on by conventional transhiatal esophagectomy. In the second group, only release of the thoracic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…A total of 10 studies 5,6,9–12,15,17–19 reported cardiac complications after esophageal cancer surgery, the findings indicated that the incidence of cardiac complications after surgery in the MAE group was lower than the TTE group (OR=0.57, 95% CI, 0.34 to 0.94, P =0.03) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A total of 10 studies 5,6,9–12,15,17–19 reported cardiac complications after esophageal cancer surgery, the findings indicated that the incidence of cardiac complications after surgery in the MAE group was lower than the TTE group (OR=0.57, 95% CI, 0.34 to 0.94, P =0.03) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 98%
“…In total, 15 studies 3,5–14,16–19 reported postoperative pulmonary complications in patients with esophageal cancer, and the results presented that the incidence of postoperative pulmonary complications in the MAE group was lower than in the TTE group (OR=0.60, 95% CI, 0.43 to 0.83, P =0.002) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While transhiatal MIE gained initial traction, concerns began to grow regarding long-term survival rates, and this technique was largely replaced by the McKeown and Ivor Lewis techniques [ 2 , 47 ]. Recent studies do exist, however, that use techniques such as mediastinoscopy to reassess safety and efficacy of minimally invasive transhiatal esophagectomy [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean volume of blood loss during the operation, mean operative time, intensive care unit stay, cardiopulmonary complications, and early postoperative complications were lower in the mediastinoscope group, and the number of resected mediastinal lymph nodes was greater. The results of this small study indicate that video mediastinoscope-assisted esophagolysis with trans-hiatal esophagectomy is safe and may reduce morbidity and mortality in ESCC patients [ 30 ]. Another risk of esophagectomy is complications from esophageal reconstruction.…”
Section: Surgerymentioning
confidence: 99%